Serotypes and antimicrobial resistance profiles of Salmonella isolates from pigs at slaughter in Kenya - Gideon M. Kikuvi; Jackson N. Ombui; Eric S. Mitema (Journal of Infection in Developing Countries)
Background: Salmonellosis is considered one of the most widespread food-borne zoonoses in industrialized as well as developing countries. The presence of Salmonella in food animals at slaughter and the consequent cross-contamination of edible carcass tissues present a significant food safety hazard.